2023
DOI: 10.1182/blood.2022015414
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell–leukemia interactions remodel drug responses, uncovering T-ALL vulnerabilities

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive and often incurable disease. To uncover therapeutic vulnerabilities, we first developed T-ALL patient-derived tumor-xenografts (PDX) and exposed PDX cells to a library of 433 clinical-stage compounds in vitro. We identified 39 broadly active compounds with anti-leukemia activity. Since endothelial cells (ECs) can alter drug responses in T-ALL, we developed an endothelial cells (ECs) / T-ALL co-culture system. We found that ECs provide pro-tumorigenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Besides, routine CNS prophylaxis is proposed, and allogeneic hematopoietic stem cell transplantation (Allo-HSCT) stands as the standard consolidation treatment in high-risk patients with an available donor. 7–11 If not treated, the leukemic cells are distributed to the blood circulation system and subsequently to vital body organs. Moreover, liquid tumors, such as leukemia, cannot be surgically removed, unlike solid tumors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, routine CNS prophylaxis is proposed, and allogeneic hematopoietic stem cell transplantation (Allo-HSCT) stands as the standard consolidation treatment in high-risk patients with an available donor. 7–11 If not treated, the leukemic cells are distributed to the blood circulation system and subsequently to vital body organs. Moreover, liquid tumors, such as leukemia, cannot be surgically removed, unlike solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Acute lymphocytic leukemia (ALL) is a kind of leukemia that develops when lymphocytes in bone marrow (BM) proliferate abnormally. [1][2][3][4][5][6][7][8] It is divided into two types based on the cell of origin: B-ALL and T-ALL. There are four stages of the treatment for ALL, which usually take two to three years: induction, consolidation, intensication, and long-term maintenance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results strengthen evidence of dynamic crosstalk between tumor-associated endothelial cells and cancer cells regulating tumor aggressiveness. 50 We have also reported that COX-2 expression was an unfavorable prognostic factor in cHL. 44 Dual inhibition of COX-2 and VEGF pathways reduced tumor metastasis and extended overall survival in several in vivo cancer models.…”
Section: Discussionmentioning
confidence: 81%
“…First developed a T-ALL/EC platform that can help elucidate the leukemia-microenvironment interactions with endothelial cells. [ 117 ] …”
Section: Single-cell Studies Provide Further Insights Into Drug Effec...mentioning
confidence: 99%